Determinants of Trust in Digital Zakat Institutions: A Study of E-Service Quality and Information Transparency Among Zakat Donors in Indonesia - Evi Khairunnisa; Asy-syura Asy-syura; Andi Al-Musawwir Syah (West Science Islamic Studies, 2026)
The digitalization of zakat services has expanded the accessibility and efficiency of zakat payments in Indonesia. However, the sustainability of digital zakat institutions depends heavily on contributors’ trust in the quality of electronic services and the transparency of institutional information. This study examines the influence of electronic service quality and information transparency on trust in digital zakat institutions among zakat contributors in Indonesia. A quantitative explanatory design was employed using a structured questionnaire distributed to 120 respondents who had paid zakat through digital platforms. Respondents were selected through purposive sampling, and all variables were measured using a five-point Likert scale. Data were analyzed using IBM SPSS Statistics Version 25 through descriptive statistics, validity and reliability tests, classical assumption tests, multiple linear regression, t-tests, F-tests, and the coefficient of determination. The results show that electronic service quality has a positive and significant effect on trust. Information transparency also has a positive and significant effect on trust. Simultaneously, both variables significantly influence trust, as indicated by an F-value of 88.714 and a significance level below 0.001. The model explains 60.2% of the variance in contributors’ trust. These findings indicate that reliable digital services, secure transactions, responsive support, accessible financial reporting, and clear zakat distribution information are important determinants of trust. Digital zakat institutions should therefore strengthen both technological service quality and transparent governance to increase contributor confidence and sustain formal zakat participation.